Can Mean-Variance Portfolio Optimization with long-only constraint help enhance momentum strategy? Evidence from S&P 100 - Le, Khanh (2020)
The paper found that, for the 10-year sample time period from 1/1/2010 to 12/27/2019, there were weakly significant (at significance level of 10%) evidence that the average excess return between winning portfolios with stock weight distributed using long-only mean-variance portfolio optimization (MVO) method and equal weight distribution (1/N) method to be positive in 3-month and 6-month holding period and strongly significant (significance level of 1%) for 12-month holding period. The same cannot be said for 6-month holding period. This implied that applying the long-only MVO method can help improve the traditional momentum strategy. However, the paper also shows that the buy-and-hold stock market index strategy (in this case is S&P 100 stock market) for medium-term holding period outperformed the winning portfolio regardless of method used for stock weight distribution in almost every case. This implies that for the time period when the economy is going well and no signal of economic downturn found, buy-and-hold stock market index is the way to go.